Prolonged incubation period of hepatitis B in a recipient of a nucleic acid amplification test‐negative hepatitis B virus window donation. Issue 9 (14th July 2021) - Matsuno, Takahiro; Matsuura, Hideaki; Fujii, Sumie; Tanaka, Ami; Satake, Masahiro; Kinoshita, Tomohiro; Tomita, Akihiro; Matsui, Yusuke; Sugiura, Yukari; Miura, Yasuo
Abstract: Background: The occurrence of transfusion‐transmitted hepatitis B virus (HBV) infection has fallen dramatically due to continuous improvements in pre‐transfusion laboratory testing. However, the characteristics of transfusion‐transmitted HBV infection caused by individual donor nucleic acid amplification test (ID‐NAT)‐negative blood products are unclear. Case Presentation: A 76‐year‐old woman with acute myeloid leukemia was diagnosed with transfusion‐transmitted HBV infection after receiving apheresis platelets derived from an ID‐NAT‐negative blood donation. This case was diagnosed definitively as transfusion‐mediated because complete nucleotide homology of a 1556 bp region of the HBV Pol/preS1‐preS2‐S genes and a 23 bp region of the HBV core promoter/precore between the donor and recipient strains was confirmed by PCR‐directed sequencing. The case is uncommon with respect to the unexpectedly prolonged HBV‐DNA incubation period of nearly 5 months after transfusion (previously, the longest period observed since the recent implementation of ID‐NAT pre‐transfusion laboratory testing in Japan was 84 days). Slow‐replicating HBV genotype A2 may contribute to the prolonged incubation period; also, the quantity of apheresis platelets delivered in a large volume of plasma, and/or the immune response of the recipient suffering from a hematological neoplasm, may have contributed to establishment of HBV infection in the recipient. This was supported by analysis of three previously documented cases of transfusion‐transmitted HBV infection by blood products derived from ID‐NAT‐negative donations in Japan. Conclusion: Continuous monitoring of HBV infection for longer periods (>3 months) may be required after transfusion of blood components from an ID‐NAT‐negative HBV window donation.